2004
DOI: 10.1016/j.ijdevneu.2004.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Differences in cell migration of cultured pituitary cells from infantile and adult rats: participation of the extracellular matrix and epidermal growth factor

Abstract: During early postnatal development in the rat, the tissue architecture of the pituitary gland shows changes, revealing an intense migration process of the cells. The aim of this work was to examine anterior pituitary cell migration over type I and III collagen as well as type IV collagen, of cultured pituitary cells from infantile rats and adult rats, and the participation of the epidermal growth factor in this process. Differences in cell migration rate over these two types of collagen substrates were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…During early postnatal development the pituitary undergoes architectural changes that involve migration and ECM remodeling. This process is regulated by epidermal growth factor (26). Furthermore, it has been shown that laminin controls the release of prolactin and gonadotropins in the normal pituitary (27).…”
Section: The Pituitary Glandmentioning
confidence: 99%
“…During early postnatal development the pituitary undergoes architectural changes that involve migration and ECM remodeling. This process is regulated by epidermal growth factor (26). Furthermore, it has been shown that laminin controls the release of prolactin and gonadotropins in the normal pituitary (27).…”
Section: The Pituitary Glandmentioning
confidence: 99%
“…Briefly, ECM remodeling is an actively synthesized or degraded process, and the presence of growth factors probably induces the variance of ECM components, or stimulates the accumulation of ECM or influences cell migration rate in ECM resulting in the change of ECM structure and stability, sequentially regulate ECM remodeling and even tissue remodeling. González et al [27] examined anterior pituitary cell migration over different type collagen of cultured pituitary cells from infantile rats and adult rats, it is indicated that infantile cells increased their migration rate with EGF stimulation, while adult cells showed a decrease in migration when the growth factor was in the medium. During migration, pituitary cells associated and arranged in clusters.…”
Section: Effects Growth Factors Exerting On Ecmmentioning
confidence: 99%
“…We have shown that cultured infantile pituitary cells migrate preferentially over collagen type I/III, and the epidermal growth factor (EGF) stimulates this behaviour. Moreover, EGF stimulation induces an increase in cell association (González et al, 2004) and cell spreading (Toral et al, 2003).The aim of the present study was to investigate more about the migration and association behaviour of SC and FS using a vertical diffusion chamber. Aliquots of 3 × 10 5 rat infantile pituitary cells were placed in the upper compartment without or with EGF (50 ng/ml) in a defined culture medium.…”
mentioning
confidence: 97%
“…We have shown that cultured infantile pituitary cells migrate preferentially over collagen type I/III, and the epidermal growth factor (EGF) stimulates this behaviour. Moreover, EGF stimulation induces an increase in cell association (González et al, 2004) and cell spreading (Toral et al, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation